1996
DOI: 10.1002/(sici)1099-1646(199607)12:4/5<391::aid-rrr436>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

A General Protocol for Restoration of Regulated Rivers

Abstract: Large catchment basins may be viewed as ecosystems in which natural and cultural attributes interact. Contemporary river ecology emphasizes the four‐dimensional nature of the river continuum and the propensity for riverine biodiversity and bioproduction to be largely controlled by habitat maintenance processes, such as cut and fill alluviation mediated by catchment water yield. Stream regulation reduces annual flow amplitude, increases baseflow variation and changes temperature, mass transport and other import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
289
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 569 publications
(300 citation statements)
references
References 125 publications
(93 reference statements)
1
289
0
2
Order By: Relevance
“…However, only recently has the importance of multiple sequential floods been emphasized for restoring the integrity of rivers downstream of reservoirs (Stanford et al, 1996), reflecting the premise of the natural flow regime as an inherent property of flowing waters (Poff et al, 1997). For instance, Kondolf and Wilcock (1996) suggested that two flood flows per year were necessary for maintaining habitat turnover of riparian areas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only recently has the importance of multiple sequential floods been emphasized for restoring the integrity of rivers downstream of reservoirs (Stanford et al, 1996), reflecting the premise of the natural flow regime as an inherent property of flowing waters (Poff et al, 1997). For instance, Kondolf and Wilcock (1996) suggested that two flood flows per year were necessary for maintaining habitat turnover of riparian areas.…”
Section: Introductionmentioning
confidence: 99%
“…The present study shows the results of multiple experimental floods over a three year period on the morphology of a canyon confined river downstream of a reservoir used for hydropower production. The floods were experimental in the sense that individual floods varied in magnitude depending on the particular needs at the time; an idea in line with adaptive management perspectives (Stanford et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Brookes and Sear, 1996;Gilvear, 1999;Kondolf, 2000;Sear, 1994), ecosystem theory (e.g. Richards et al, 2002;Stanford et al, 1996), hydraulic engineering (e.g. Shields, 1996) and detailed design procedures (Miller et al, 2001;Shields et al, 2003;Wheaton et al, 2004b).…”
Section: Approaches To Restorationmentioning
confidence: 99%
“…Using a 'process-based' approach can make intuitive sense for passive approaches to restoration. For example, providing fl ow releases from a reservoir to mimic a natural hydrograph and encourage mobilisation and reorganisation of sediments, may restore the processes that 'allow the river to do the work' (Stanford et al, 1996;Trush et al, 2000). However, active approaches are considered favourable when natural or passive recovery may take an unacceptably long time (Montgomery and Bolton, 2003).…”
Section: Approaches To Restorationmentioning
confidence: 99%
“…A range of variation of the indices may then be set, based upon ±1 standard deviation from the mean or between the 25th and 75th percentiles. Variability in stream fl ow is essential in sustaining ecosystem integrity (long term maintenance of biodiversity and productivity) and resiliency (the capacity to endure natural and human disturbances - Stanford et al, 1996). This method is intended to defi ne interim standards, which can be monitored and revised.…”
Section: Desk Top Analysismentioning
confidence: 99%